Introduction to the Special Issue Linguistic Practices in Heritage Language Acquisition - Ekaterina Protassova; Maria Yelenevskaya (Languages)
Linguistic practices in heritage language (HL) acquisition refer to the ways in which language is used, managed, and passed on within families, communities, or institutions to help children, adolescents, and young adults learn and maintain it [...]